Case report of a very rare Trauma Combination: Concomitant Complex Ipsilateral ankle fracture associated with tibia shaft fracture - Başdelioğlu, Koray (Eastern Journal of Medical Sciences, 2019)
There is a relationship between tibial shaft fractures and ankle injuries. Complex ankle injuries including fractures and syndesmosis injuries associated with ipsilateral tibial fractures are uncommon.  In this case report, a four-combination injury including oblique-spiral tibial shaft fracture [TSF], posterior malleolar fracture [PMF], lateral malleolar fracture [LMF], and anteroinferior tibiofibular ligament [AITFL] avulsion in ankle are presented. A 45-year-old female patient was reported to the Department of Orthopedics with the diagnosis of tibia fracture by the emergency department. Ankle injury was noted during clinical examinationa and evaluation of xray. CT study used determine the components of ankle injury and to plan surgery showed distal third oblique-spiral TSF, LMF, PMF, and AITFL avulsion. The next day, the patient underwent open reduction and internal fixation with the fluoroscopic guidance, for all fractures. Only the screw to the posterior malleolus was sent percutaneously under fluoroscopy. No complication and untoward event developed during and after the operation. The fractures reached both radiological and clinical bony union at 4 months. Ankle injuries such as LM fractures, PM fractures and AITFL avulsion fractures, which may be associated with oblique spiral type TSFs, are rarely seen or neglected. It is clinically important to recognize the four-combination injury preoperatively as unsuccessful reduction or fixing of the four-combination injury in the anatomic position may increase the risk of posttraumatic arthritis. Therefore, ankle fracture and syndesmosis injuries which is associated with tibia shaft fracture should not be missed and should treated appropriately.